Theory And Concept Of Business Ethic In International Relations Studies - S, Dedik Fitra; N, Praja Firdaus; Gege, Rendy; ., Trisfani (Global and Policy Journal of International Relations, 2014)
ABSTRACTIn the discourse of business and global corporations, the study of ethics in business and globalcorporations are rarely found. Hence, this paper will discuss the ethics in business and globalcorporations. This paper firstly examines the theories and conceptual backrounds of ethics inthe discipline of International Relations. Then the paper starts to discuss the business ethics interms of international political economy. Authors found that the discourse of ethics in businessand global corporations could be examined through three paths. They are ethics and CSR,ethics and global governance, and also ethics and the new millennium. Last, the paperconcludes that business ethics are important. They are vital because the operations and thebehaviors of the global corporations reflect their business and economical interests.Keywords: The Ethics, Business and Global Corporations, International Political Economy,CSR, Global Governance, and The New Milenium.DOI:https://doi.org/10.33005/jgp.v2i02.2069